No association between thbmass and polymorphisms in the HBB gene in endurance athletes - Malczewska-Lenczowska, J.; Orysiak, J.; Majorczyk, E.; Pokrywka, A.; Kaczmarski, J.; Szygula, Z.; Sitkowski, D. (Biology of Sport, 2014)
The aim of this study was to examine the association between tHbmass and HBB gene polymorphisms in athletes of endurance disciplines. Eighty-two well-trained athletes (female n=36, male n=46), aged 19.3 ± 2.7 years, representing cross country skiing (n=37) and middle- and long-distance running (n=45), participated in the study. Genotyping for 2 polymorphisms in the HBB gene (- 551C/T and intron 2, +16 C/G) was performed using restriction fragment length polymorphism analysis. Total haemoglobin mass (tHbmass) was determined by the optimized carbon monoxide rebreathing method. Blood morphology, indices of iron status (ferritin, transferrin receptor and total iron binding capacity) and C reactive protein were also determined. No differences were found in the HBB genotype and allele frequencies between male and female athletes. Regardless of the polymorphisms, no relationships were found between HBB genotypes as well as alleles and relative values of tHbmass, expressed per body mass (g/kg BM), both in female and male athletes. Our results demonstrated that -551 C/T and intron 2, +16 C/G polymorphisms of the HBB gene have no association with total haemoglobin mass in endurance athletes. It cannot be ruled out that several polymorphisms, each with a small but significant contribution, may be responsible for the amount of haemoglobin.